GAYA BAHASA DALAM AKUN TIKTOK @DAFFAARIQQQQ - Agatha, Maidah Aisa; Damayanti, rini (Universitas Wijaya Kusuma Surabaya, 2025)
This study aims to describe the form of language style in the comment column of the tiktok @daffaariqqqq account and the factors that form the emergence of language style in the comment column of the tiktok @daffaariqqq account. This research is a type of qualitative descriptive research. The data source in this study is tiktok user comments on the @daffaariqqqq account. Data collection uses documentation techniques in the form of screen captures and then researchers process the data using reading techniques and note taking techniques. The data collection instrument used in this research is a device used to view the tiktok account @daffaariqqqq.The results showed that there was a use of satire language style by tiktok social media users found (1) The form of using ironic satire language style includes situational irony and verbal irony. Cynicism is found in the form of social criticism. Sarcasm is found in the form of action, form of designation, and form of nature. (2) The factors that form the emergence of satire language styles that researchers found were the annoyance of tiktok users, showing existence, and expressing opinions.